Physician-patient communication in at outpatient of pediatrics university hospital - Lira, Haline G.; Machado, Camila V. B.; Del Ciampo, Ieda R. L.; Del Ciampo, Luiz A. (Medicina (Ribeirao Preto), 2015)
Introduction: the doctor-patient relationship depends on factors related to individuals and their social and cultural conditions that enable the meeting of these two characters. Objective: to examine some aspects related to the care of children attending the outpatient clinics of the university hospital, with respect to the contact and dialogue with the clinical staff. Methodology: retrospective, observational and descriptive study developed in the clinics of the Hospital das Clínicas, Faculty of Medicine of Ribeirão Preto - USP, through interviews with mothers of children awaiting medical care. We used a questionnaire with questions concerning to child (age, gender, followup time in service), to mother (age, educational level and marital status) and to relationship with the physician, understanding the guidelines, positives and negative attention and suggestions. The study was approved by the Research Ethics Committee of the Hospital of the Faculty of Medicine of Ribeirão Preto, University of São Paulo. Results: 118 mothers participated median age was 32 years, 53.3% married and 22.8% unmarried. Among children, 57.6% were female and 42.3% male. The median educational level of the mothers indicated a high school degree and the mean follow-up in outpatient clinics was 2 years and 1 month. 50% of mothers reported that the technical terminology was the main cause of the difficulty of understanding during the consultation, 34.7% highlighted the attention given by the doctor as the biggest positive, while 57,6% pointed out that the delay was the main negative factor during service. Conclusions: the difficulties of communication between doctor and patient and the host were considered important in the care offered by the university hospital, and should be part of the working professional context.